A comprehensive review on elucidating the host disease resistance mechanism from the perspective of the interaction between cotton and Verticillium dahliae - Yalin Zhang; Lihong Zhao; Dongpo Li; Ziming Li; Hongjie Feng; Zili Feng; Feng Wei; Jinglong Zhou; Zhiying Ma; Jun Yang; Heqin Zhu (Journal of Cotton Research)
Abstract Verticillium wilt, caused by the infamous pathogen Verticillium dahliae, presents a primary constraint on cotton cultivation worldwide. The complexity of disease resistance in cotton and the largely unexplored interaction dynamics between the cotton plant host and V. dahliae pathogen pose a crucial predicament for effectively managing cotton Verticillium wilt. Nevertheless, the most cost-effective approach to controlling this disease involves breeding and cultivating resistant cotton varieties, demanding a meticulous analysis of the mechanisms underlying cotton’s resistance to Verticillium wilt and the identification of pivotal genes. These aspects constitute focal points in disease-resistance breeding programs. In this review, we comprehensively discuss genetic inheritance associated with Verticillium wilt resistance in cotton, the advancements in molecular markers for disease resistance, the functional investigation of resistance genes in cotton, the analysis of pathogenicity genes in V. dahliae, as well as the intricate interplay between cotton and this fungus. Moreover, we delve into the future prospects of cutting-edge research on cotton Verticillium wilt, aiming to proffer valuable insights for the effective management of this devastating fungus.